Here to stay?: Policy changes in alcohol home delivery and "to-go" sales during and after COVID-19 in the United States - Lemp, Julia M.; Kilian, Carolin; Probst, Charlotte (Drug and alcohol review, 2024)
During the early phase of the COVID-19 pandemic, legislative changes that expanded alcohol home delivery and options for "to-go" alcohol sales were introduced across the United States to provide economic relief to establishments and retailers. Using data from the Alcohol Policy Information System, we examined whether these changes have persisted beyond the peak phase of the COVID-19 emergency and explored the implications for public health. Illustration of state-level policy data reveals that the liberalisation of alcohol delivery and "to-go" alcohol sales has continued throughout a 2-year period (2020 and 2021), with indications that many of these changes have or will become permanent after the pandemic. This raises concerns about inadequate regulation, particularly in preventing underage access to alcohol, and ensuing changes in drinking practices. In this commentary, we highlight the need for rigorous empirical evaluation of the public health impact of this changing policy landscape and underscore the potential risks associated with increased alcohol availability, including a corresponding increase in alcohol-attributable mortality and other alcohol-related harm, such as domestic violence. Policy makers should carefully consider public health consequences, whose costs may surpass short-term economic interests in the long term.